Răspuns :
[tex]A(-2,2)[/tex]
[tex]B(1,0)[/tex]
[tex]C(-1,1)[/tex]
[tex]AB=\sqrt{{(x_{B}-x_{A})}^{2}+{(y_{B}-y_{A})}^{2}}[/tex]
[tex]AB=\sqrt{{(1 + 2)}^{2}+{(0-2)}^{2}}[/tex]
[tex]AB=\sqrt{{3}^{2}+{(-2)}^{2}}[/tex]
[tex]AB=\sqrt{9+4}[/tex]
[tex]AB=\sqrt{13}[/tex]
[tex]AC=\sqrt{{(x_{C}-x_{A})}^{2}+{(y_{C}-y_{A})}^{2}}[/tex]
[tex]AC=\sqrt{{( - 1 + 2)}^{2}+{(1-2)}^{2}}[/tex]
[tex]AC=\sqrt{{1}^{2}+{(-1)}^{2}}[/tex]
[tex]AC=\sqrt{1 + 1}[/tex]
[tex]AC=\sqrt{2}[/tex]
[tex]BC=\sqrt{{(x_{C}-x_{B})}^{2}+{(y_{C}-y_{B})}^{2}}[/tex]
[tex]BC=\sqrt{{( - 1-1)}^{2}+{(1-0)}^{2}}[/tex]
[tex]BC=\sqrt{{( - 2)}^{2}+{1}^{2}}[/tex]
[tex]BC=\sqrt{4+1}[/tex]
[tex]BC=\sqrt{5}[/tex]
Pentru arie folosim formula lui Heron :
[tex]AB=a[/tex]
[tex]AC=b[/tex]
[tex]BC=c [/tex]
[tex]p = \frac{a + b + c}{2} [/tex]
[tex]p = \frac{ \sqrt{13} + \sqrt{2} + \sqrt{5} }{2} [/tex]
[tex]A=\sqrt{p(p-a)(p-b)(p-c)}[/tex]
[tex]A=\sqrt{ \frac{ \sqrt{13} + \sqrt{2} + \sqrt{5} }{2} ( \frac{ \sqrt{13} + \sqrt{2} + \sqrt{5} }{2} - \sqrt{13} )( \frac{ \sqrt{13} + \sqrt{2} + \sqrt{5} }{2} - \sqrt{2} )( \frac{ \sqrt{13} + \sqrt{2} + \sqrt{5} }{2} - \sqrt{5} )} [/tex]
[tex]A=\sqrt{ \frac{ \sqrt{13} + \sqrt{2} + \sqrt{5} }{2} \times \frac{ - \sqrt{13} + \sqrt{2} + \sqrt{5} }{2} \times \frac{ \sqrt{13} - \sqrt{2} + \sqrt{5} }{2} \times \frac{ \sqrt{13} + \sqrt{2} - \sqrt{5} }{2} }[/tex]
[tex]A = \sqrt{ \frac{( \sqrt{13} + \sqrt{2} + \sqrt{5} )( - \sqrt{13} + \sqrt{2} + \sqrt{5} )( \sqrt{13} - \sqrt{2} + \sqrt{5} )( \sqrt{13} + \sqrt{2} - \sqrt{5} )}{16} } [/tex]
[tex]( \sqrt{13} + \sqrt{2} + \sqrt{5} )( - \sqrt{13} + \sqrt{2} + \sqrt{5} ) = - 1 + \sqrt{26} + \sqrt{65} - \sqrt{26} + 2 + \sqrt{10} - \sqrt{65} + \sqrt{10} + 5 = 6 + 2 \sqrt{10} [/tex]
[tex]( \sqrt{13} - \sqrt{2} + \sqrt{5} )( \sqrt{13} + \sqrt{2} - \sqrt{5} ) = 13 + \sqrt{26} - \sqrt{65} - \sqrt{26} - 2 + \sqrt{10} + \sqrt{65} + \sqrt{10} - 5 = 6 + 2 \sqrt{10} [/tex]
[tex]A = \sqrt{ \frac{(6 + 2 \sqrt{10} )(6 + 2 \sqrt{10}) }{16} } [/tex]
[tex]A = \sqrt{ \frac{ {(6 + 2 \sqrt{10} )}^{2} }{ {4}^{2} } } [/tex]
[tex]A = \frac{6 + 2 \sqrt{10} }{ 4} [/tex]
[tex]A = \frac{2(3 + \sqrt{10} )}{4} [/tex]
[tex]A = \frac{3 + \sqrt{10} }{2} [/tex]
[tex]B(1,0)[/tex]
[tex]C(-1,1)[/tex]
[tex]AB=\sqrt{{(x_{B}-x_{A})}^{2}+{(y_{B}-y_{A})}^{2}}[/tex]
[tex]AB=\sqrt{{(1 + 2)}^{2}+{(0-2)}^{2}}[/tex]
[tex]AB=\sqrt{{3}^{2}+{(-2)}^{2}}[/tex]
[tex]AB=\sqrt{9+4}[/tex]
[tex]AB=\sqrt{13}[/tex]
[tex]AC=\sqrt{{(x_{C}-x_{A})}^{2}+{(y_{C}-y_{A})}^{2}}[/tex]
[tex]AC=\sqrt{{( - 1 + 2)}^{2}+{(1-2)}^{2}}[/tex]
[tex]AC=\sqrt{{1}^{2}+{(-1)}^{2}}[/tex]
[tex]AC=\sqrt{1 + 1}[/tex]
[tex]AC=\sqrt{2}[/tex]
[tex]BC=\sqrt{{(x_{C}-x_{B})}^{2}+{(y_{C}-y_{B})}^{2}}[/tex]
[tex]BC=\sqrt{{( - 1-1)}^{2}+{(1-0)}^{2}}[/tex]
[tex]BC=\sqrt{{( - 2)}^{2}+{1}^{2}}[/tex]
[tex]BC=\sqrt{4+1}[/tex]
[tex]BC=\sqrt{5}[/tex]
Pentru arie folosim formula lui Heron :
[tex]AB=a[/tex]
[tex]AC=b[/tex]
[tex]BC=c [/tex]
[tex]p = \frac{a + b + c}{2} [/tex]
[tex]p = \frac{ \sqrt{13} + \sqrt{2} + \sqrt{5} }{2} [/tex]
[tex]A=\sqrt{p(p-a)(p-b)(p-c)}[/tex]
[tex]A=\sqrt{ \frac{ \sqrt{13} + \sqrt{2} + \sqrt{5} }{2} ( \frac{ \sqrt{13} + \sqrt{2} + \sqrt{5} }{2} - \sqrt{13} )( \frac{ \sqrt{13} + \sqrt{2} + \sqrt{5} }{2} - \sqrt{2} )( \frac{ \sqrt{13} + \sqrt{2} + \sqrt{5} }{2} - \sqrt{5} )} [/tex]
[tex]A=\sqrt{ \frac{ \sqrt{13} + \sqrt{2} + \sqrt{5} }{2} \times \frac{ - \sqrt{13} + \sqrt{2} + \sqrt{5} }{2} \times \frac{ \sqrt{13} - \sqrt{2} + \sqrt{5} }{2} \times \frac{ \sqrt{13} + \sqrt{2} - \sqrt{5} }{2} }[/tex]
[tex]A = \sqrt{ \frac{( \sqrt{13} + \sqrt{2} + \sqrt{5} )( - \sqrt{13} + \sqrt{2} + \sqrt{5} )( \sqrt{13} - \sqrt{2} + \sqrt{5} )( \sqrt{13} + \sqrt{2} - \sqrt{5} )}{16} } [/tex]
[tex]( \sqrt{13} + \sqrt{2} + \sqrt{5} )( - \sqrt{13} + \sqrt{2} + \sqrt{5} ) = - 1 + \sqrt{26} + \sqrt{65} - \sqrt{26} + 2 + \sqrt{10} - \sqrt{65} + \sqrt{10} + 5 = 6 + 2 \sqrt{10} [/tex]
[tex]( \sqrt{13} - \sqrt{2} + \sqrt{5} )( \sqrt{13} + \sqrt{2} - \sqrt{5} ) = 13 + \sqrt{26} - \sqrt{65} - \sqrt{26} - 2 + \sqrt{10} + \sqrt{65} + \sqrt{10} - 5 = 6 + 2 \sqrt{10} [/tex]
[tex]A = \sqrt{ \frac{(6 + 2 \sqrt{10} )(6 + 2 \sqrt{10}) }{16} } [/tex]
[tex]A = \sqrt{ \frac{ {(6 + 2 \sqrt{10} )}^{2} }{ {4}^{2} } } [/tex]
[tex]A = \frac{6 + 2 \sqrt{10} }{ 4} [/tex]
[tex]A = \frac{2(3 + \sqrt{10} )}{4} [/tex]
[tex]A = \frac{3 + \sqrt{10} }{2} [/tex]